PENGARUH FLY ASH LIMBAH PADAT PABRIK MINYAK NABATI DALAM KOMPOSIT PAVING BLOCK - Broerie Pojoh (Jurnal Penelitian Teknologi Industri, 2021)
Fly ash solid waste was produced in considerable amount from vegetable oil industry. Those waste could not be buried in any unintended landfill. Without those area to bury in, fly ash solid waste could then create many problems such as less open space and aesthetic, and also dust pollution. A research to employ fly ash solid waste for making paving block and study its effect on its quality has been implemented. This research using different application of fly ash, coarse sand, with constant application of fine sand aggregate and portland cement. The result showed that fly ash solid waste could be employed to make paving block as a filler. Physical analysis was conducted from SNI. 03-0691-1996, resulted paving block A1B2 had highest pressure strength (22.34 MPa) while paving block A3B3 had lowest pressure strength (18.58 MPa). Water absorbing property for all treatments varied from 2.41-4.48%. From physical analysis, paving block of A1B1, A1B2, A1B3, A2B1, A2B2, and A2B3 were included in B quality requirement (for parking lot purpose). On the other hand, paving block of A3B2 and A3B3 were included in C quality requirement (for sidewalk purpose). The best composition to produce paving block was A1B2, which was 2 parts of fly ash, 8 part of sand and 2 parts of portland cement, resulted paving block with pressure strength of 22.34 MPa and water absorbtion of 2.60%. Research also showed that the use of fly ash increased the total production of paving block so it could improve the revenue for producer.Keywords: fly ash, solid waste, composite, paving block